2021
DOI: 10.1155/2021/6691705
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Early Endoscopic Ultrasound-Guided Transluminal Drainage for Postoperative Pancreatic Fistula

Abstract: Background. Endoscopic ultrasound-guided transluminal drainage (EUS-TD) is generally performed 4 weeks after disease onset for evacuating pancreatic fluid collections. However, the optimal timing for conducting the procedure in those diagnosed with postoperative pancreatic fistula (POPF) has not been established. We aimed to elucidate the efficacy and safety of early EUS-TD procedures for treating POPF. Methods. We retrospectively reviewed patients diagnosed with POPF who underwent EUS-TD in the Kyushu Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…A number of studies have demonstrated the safety and efficacy of early EUS-guided drainage for POFC. EUS-guided drainage in some of these studies was performed within two weeks of surgery and sometimes even as early as three days after surgery [19]. These studies are limited by their retrospective nature, small sample sizes, and potential for selection bias [7,[16][17][18][19]23,24].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies have demonstrated the safety and efficacy of early EUS-guided drainage for POFC. EUS-guided drainage in some of these studies was performed within two weeks of surgery and sometimes even as early as three days after surgery [19]. These studies are limited by their retrospective nature, small sample sizes, and potential for selection bias [7,[16][17][18][19]23,24].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Subgroup analysis in one of these studies even demonstrated no significant difference in terms of clinical outcomes or complications for patients undergoing acute drainage within 14 days of surgery [17]. These results were then replicated in dedicated studies comparing acute EUSguided drainage within two weeks of surgery to those performed after two weeks [18,19]. These studies are summarised in Table 2 below.…”
Section: Timing For Pofc Drainagementioning
confidence: 90%
See 3 more Smart Citations